2019
DOI: 10.1088/1757-899x/646/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Promotes the Evolution of English Writing Evaluation Model

Abstract: On the background of “Internet +” era, the domestic higher education is showing the trend of artificial intelligence. The reliability and scientificity of computer intelligent evaluation are further carried out, and the mode of intelligent evaluation and data analysis in optimizing the precise teaching of English writing is explored, which can lay a foundation for the large-scale use of the technology. Based on data-driven theory, this study further analyzed the role of AI in promoting in-depth learning by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The results showed that AI was an effective intervention for improving positive and decreasing negative emotions in L2 students (Su et al, 2019). AIs provide in-depth analytical assessments and immediate feedback, which can induce a series of emotions in academic settings.…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that AI was an effective intervention for improving positive and decreasing negative emotions in L2 students (Su et al, 2019). AIs provide in-depth analytical assessments and immediate feedback, which can induce a series of emotions in academic settings.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, AI can also take the form of chatbots that facilitate communication, to improve one's language skills [22]. Then, in other studies, the use of AI was shown to improve writing skills and lower the fear of writing [23]. Fear in the use of foreign languages, especially speaking to students can cause student achievement scores in learning to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Individualized and oral English learning stimulates students' interest in English learning as well as improves the learning atmosphere in English classrooms. This is not only a significant reflection of the value of English teaching and learning in the education industry, but also an in-depth exploration of the value of modern information technology [Su et al 2019].…”
Section: Figure 1: Typical Nlp For Education Research Lifecyclementioning
confidence: 98%